The enduring pursuit of science in America - Neil H. Shubin (Science, 2026)
Imagine an American organization that convenes scientific experts not to advance any ideology or interest but to provide the nation with a clear understanding of complex problems. Imagine this body would follow the evidence rather than the headlines and earn its authority not through rhetoric or persuasion but careful and rigorous analysis and transparent processes. This institution exists—although its work faces pressing challenges—and it is more urgently needed today than at any point in living memory.